Design and implementation of a didactic module for teaching the parameters of impact on the performance of a wind turbine (Innovation & Development in Engineering and Applied Science, 2024)
Currently, the study of renewable energy sources is important in order to evaluate their performance and know their limitations. The objective of this research is to design and build a teaching module of a wind tunnel, for the evaluation and teaching of the performance of a wind turbine, by varying the wind speed. The proposed teaching module is made up of a 600 W wind turbine, a 200 W fan, a wind tunnel and sensors to collect information on current, voltage, temperature, humidity and wind speed. These signals are displayed in a graphical interface where the student can observe the behavior of these variables through curves that are built through the acquisition of data in real time. This allows students to evaluate the effect of wind speed on the performance of the wind turbine in generating electrical energy. The operating module starts when the fan is turned on and generates wind with an approximate speed of 4.5 m/s. This flow is regulated through a dimmer that allows the wind speed to be increased progressively, allowing the effect of wind speed on the wind turbine to be observed.
Keywords: wind tunnel; wind turbine; data acquisition; teaching module